Assyria to Iberia : at the dawn of the Classical Age - Aruz, Joan 1942-.; Metropolitan Museum of Art (New York: The Metropolitan Museum of Art.)
This comprehensive book explores the spectacular art of the first millennium B.C. from the Near East to Western Europe. This was the world of Odysseus, in which trade proliferated with Phoenician merchants; of King Midas, whose tomb was adorned with treasures; and of the Bible, whose stories are illuminated by recent artistic and archaeological discoveries. It was also a time of rich cultural exchange across the Mediterranean and Near East as diverse populations interacted through trade, travel and migration. This book showcases masterpieces that reflect the cultural encounters of this era. Stunning details convey the significance of more than 300 objects drawn from collections around the globe. These objects include carved reliefs from the majestic palaces of ancient Assyria, Phoenician fine bronze metalwork and carved ivories, Egyptian statues, and luxurious jewelry. Texts by over 80 international scholars provide a compelling picture of this fascinating period, one that is essential to understanding the origins of Western culture and art.--publisher's web site. This comprehensive book explores the spectacular art of the first millennium B.C. from the Near East to Western Europe. This was the world of Odysseus, in which trade proliferated with Phoenician merchants; of King Midas, whose tomb was adorned with treasures; and of the Bible, whose stories are illuminated by recent artistic and archeological discoveries. It was also a time of rich cultural exchange across the Mediterranean and Near East as diverse populations interacted through trade, travel, and migration. Assyria to Iberia showcases masterpieces that reflect the cultural encounters of this era. Stunning details convey the beauty and significance of more than 300 objects drawn from collections around the globe. These objects include carved reliefs from the majestic palaces of ancient Assyria, Phoenician fine bronze metalwork and carved ivories, and luxurious jewelry. Texts by over 80 international scholars provide a compelling picture of this fascinating period, one that is essential to understanding the origins of Western culture and art.
Catalog of an exhibition held at The Metropolitan Museum of Art, New York, September 22, 2014 - January 4, 2015.
Assyria to Iberia at the Dawn of the Classical Age (Exhibition) (2014-2015 : New York, N.Y.)
Includes bibliographical references (pages 376-411) and index.
Keywords: Art, Ancient -- Exhibitions; Civilization, Ancient -- Exhibitions; Art, Ancient; Middle East -- Antiquities -- Exhibitions; History of art: BCE to c 500 CE, ancient & classical world; ART / History / Ancient & Classical; ART / Collections, Catalogs, Exhibitions / Permanent Collections; ART / Middle Eastern -- Middle Eastern; Mediterranean Region -- Antiquities -- Exhibitions